Prospective comparison of costs and short term health outcomes of surgical versus device closure of atrial septal defect in children. Issue 1 (1st July 2002) - Hughes, M L; Maskell, G; Goh, T H; Wilkinson, J L
Abstract : Objective: To compare surgical and device closure of isolated secundum atrial septal defect (ASD) in terms of hospital costs, clinical outcome, and impact on the patient and family. Design: Prospective, observational study. Setting: Paediatric tertiary referral centre. Patients: Consecutive local children with a secundum ASD, admitted between 1 May 1999 and 1 May 2001. Methods: Parents completed a standardised questionnaire at recruitment (on admission), at discharge, and one month after the procedure. Clinical and hospital generated cost data were collated at discharge. Results: 62 children were included in the analysis: 19 who underwent surgical repair and 43 who underwent device closure with the Amplatzer septal occluder. Median procedure times and hospital stay were significantly longer for surgical patients (170 (147 to 180) v 92 (70 to 115) minutes and 88 (78 to 112) v 29 (28 to 30) hours, respectively; p < 0.01). There was no difference in the complication rate. No device patients required intensive care or blood products. The median values for postoperative pain score, analgesia use, and convalescence time were greater for surgical patients. The median cost of each procedure was similar, but higher nursing and laboratory costs contributed to a slightly greater total cost for surgical repair (Aus$12 969 ($11 569 to $14 215) v Aus$11 845 ($10 669 to $12 555), p = 0.03). Conclusions: Device closure of ASD involves a shorter hospital stay, causes less discomfort and familial disturbance, and carries less cost than surgical closure. However, there should be guarded acceptance of this technique until long term data are available.